Social tagging in a linked data environment - Neal, Diane Rasmussen; Spiteri, Louise F. (Facet Publishing, 2019)
"Social tagging (including hashtags) is used over platforms such as Twitter, Facebook, Instagram, Pinterest, WordPress, Tumblr and YouTube across countries and cultures, meaning that one single hashtag can link information from a variety of resources. This new book explores social tagging as a potential form of linked data and shows how it can provide an increasingly important way to categorize and store information resources. The internet is moving rapidly from the social web embodied in Web 2.0, to the semantic web (Web 3.0), where information resources are linked to make them comprehensible to both machines and humans. Traditionally, library discovery systems have pushed information, but did not allow for any interaction with the users of the catalogue, while social tagging provides a means to help library discovery systems become social spaces where users could input and interact with content. The editors and their international contributors explore key issues including the use of hashtags in the dissemination of public policy, the use of hashtags as information portals in library catalogues, social tagging in enterprise environments, the linked data potential of social tagging, [and] sharing and disseminating information needs via social tagging. Social Tagging in a Linked Data Environment will be useful reading for practising library and information professionals involved in electronic access to collections, including cataloguers, system developers, information architects and web developers"--